Mutations in OsDET1, OsCOP10, and OsDDB1 confer embryonic lethality and alter flavonoid accumulation in Rice (Oryza sativa L.) seed - Kim, Backki; Lee, Yoonjung; Nam, Ji-Young; Lee, Gileung; Seo, Jeonghwan; Lee, Dongryung; Cho, Yoo-Hyun; Kwon, Soon-Wook; Koh, Hee-Jong (Frontiers in Plant Science, 2022)
Morphological and biochemical changes accompanying embryogenesis and seed development are crucial for plant survival and crop productivity. Here, we identified a novel yellowish-pericarp embryo lethal (yel) mutant of the japonica rice cultivar Sindongjin (Oryza sativa L.), namely, yel-sdj. Seeds of the yel-sdj mutant showed a yellowish pericarp and black embryo, and were embryonic lethal. Compared with wild-type seeds, the yel-sdj mutant seeds exhibited significantly reduced grain size, grain weight, and embryo weight, and a remarkably lower rate of embryo retention in kernels subjected to milling. However, the volume of air space between embryo and endosperm, density of embryo, and total phenolic content and antioxidant activity of mature grains were significantly higher in the yel-sdj mutant than in the wild type. Genetic analysis and mapping revealed that the yel-sdj mutant was nonallelic to the Oscop1 null mutants yel-hc, yel-cc, and yel-cc, and its phenotype was controlled by a single recessive gene, LOC_Os01g01484, an ortholog of Arabidopsis thaliana DE-ETIOLATED 1 (DET1). The yel-sdj mutant carried a 7 bp deletion in the second exon of OsDET1. Seeds of the Osdet1 knockout mutant, generated via CRISPR/Cas9-based gene editing, displayed the yel mutant phenotype. Consistent with the fact that OsDET1 interacts with CONSTITUTIVE PHOTOMORPHOGENIC 10 (OsCOP10) and UV-DAMAGED DNA BINDING PROTEIN 1 (OsDDB1) to form the COP10-DET1-DDB1 (CDD), seeds of Oscop10 and Osddb1 knockout mutants also showed the yel phenotype. These findings will enhance our understanding of the functional roles of OsDET1 and the CDD complex in embryogenesis and flavonoid biosynthesis in rice seeds.